Pengaruh Profitabilitas, Ukuran Perusahaan, dan Kepemilikan Manajerial terhadap Praktik Perataan Laba (Income Smoothing) - Maotama, Ngurah Surya; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 30 No 7 (2020), 2020)
The research aims to obtain empirical evidence about the effect of profitability, company size, and managerial ownership on income smoothing practices (Income Smoothing). This research was conducted at property and real estate companies listed on the Indonesia Stock Exchange in 2015-2018. Sampling technique using purprosive sampling method obtained 18 selected companies to be sampled with 3 years of observation so as to get a total sample of 54. Hypothesis testing was tested using logistic regression analysis techniques. positive about income smoothing practices (Income Smoohing). Keywords : Income Smoothing Practices; Profitability; Company Size; Managerial Ownership.